Simultaneous thermodynamic and dynamical characterisation using in situ calorimetry with neutron spectroscopy - Fornalski, D.; García Sakai, V.; Postorino, S.; Silverwood, I.; Goodway, C.; Bones, J.; Kirichek, O.; Fernandez-Alonso, F. (Физика низких температур, 2019)
Both Differential Scanning Calorimetry (DSC) and Quasi-elastic Neutron Scattering (QENS) are powerful analytical tools actively used in studies of phase transitions in complex solid and liquid systems. DSC is typically used to map phase transition temperatures and identify sample states, and QENS provides information on the molecular scale dynamical motions, such as molecular self-diffusion or glassy dynamics, associated with such transitions. Both techniques provide highly valuable complementary information about the sample and in many cases it would be advantageous to measure in parallel with a view to linking the two observables. The biggest challenge is that the cell design which differs greatly between the two methods. Here we present a first attempt at designing a cryogenic system which will allow the simultaneous measurement of calorimetric transitions and QENS measurements, as tested on the neutron spectrometer IRIS at ISIS neutron scattering facility. The system temperature range is from 10 K to 300 K. We present and discuss the initial design of the system, preliminary test results, current challenges and limitations, and future directions.